Indução tributária, patrimônio de afetação da incorporação imobiliária e a efetivação do direito à moradia. - Nascimento, Jose Fernandes do (2015)
The right to housing is a human right, as recognized by international law, and a fundamental social right, as is provided for in the Federal Constitution. It exercises both the role of law and defense of the right to benefits, divided into these materials and regulatory benefits. In a normative activity of real estate has proven to be an effective instrument of access to decent housing. It is an activity which is characterized by the construction and sale, total or partial, of real estate units autonomous being constructed or still under construction. And why involve the disposal of future thing, the incorporative business presents a high risk of loss to the purchasers, which can be alleviated significantly with the adoption of the appropriated assets of the real estate regime, instrument that is characterized by the segregation of the net assets of each incorporation of general assets of the developer. It protects the purchaser of the real estate unit against any bankruptcy or insolvency civil of the developer, or undue delay in execution of work. Occurring of these situations, the general meeting shall decide the buyer or the continuation of the work by the liquidation of net assets. In either case, the developer is away from the direction of the project and representatives commission of the purchasers assumes administration of the enterprise affected, if feasible the construction, continue execution of the work, or liquidate the net assets of their incorporation affected. However, as the regime of affectation is of optional implantation, the discretion of the developer, it needs stimulus to offset the restrictions arising from the regime of affectation. For this purpose, the special tax regime was instituted for such appropriated assets, with the aim of simplifying and reducing the tax burden of affected incorporation in relation to federal taxes levied on the incorporative activity, compared with the usual forms of taxation by the developer of real income regime or the presumed profit regime.